Impact Of Assistive Technology Intervention On Visually Impaired Student Performance In Kiswahili In Public Primary Teachers College In Kenya - Mutua, Francis Bisi (My University, 2013)
The right to education is universal to all including those with disabilities.Students with visual impairments can struggle with a wide variety of challenges in a mainstreamed classroom setting.AT intervention by use of assistive devices in teaching,use of assistive methods,taking care of VI severity and boosting positively the student-teacher related factors improve their performance.The purpose of this study was to examine the impact of assistive technology intervention on visually impaired students’ performance in Kiswahili in public primary TCs Kenya.